Impact of mental illness on in-patient hospital costs for somatic disorders and associated factors. (13th November 2019) - Michel, M; Hammami, A J; Chevreul, K
Abstract: Background: People suffering from mental disorders are in poorer somatic health that the general population. This is due in part to poor quality of care in primary care settings, which can in turn have a major impact on hospitals and healthcare systems, in particular in terms of costs. Our objective was to assess the economic burden of acute care admissions for somatic diseases in patients with a mental illness compared to other patients and analyse the factors associated with it. Methods: An exhaustive study using French hospital discharge databases was carried out between 2009 and 2013. Total acute hospital costs were calculated from the all payer perspective (statutory health insurance, private health insurances and patient out-of pocket payments). A multivariate regression modelled the association between mental illness and hospital costs while adjusting for other explanatory variables, with and without interaction terms. Results: 37, 458, 810 admissions were included in the analysis. 1, 163, 972 patients (6.54%) were identified as being mentally ill. Mean total hospital costs at five years per patient were €8, 114. Costs per mentally ill patient were on average 34% higher than for a non-mentally patient (€10, 637 vs. €7, 949). A longitudinal analysis of costs showed a widening of the gap between the two groups as time went by, from 1.60% in 2009 to 10.51% in 2013. In the multivariate model, mental disorders were significantly associated with increased costs, and interaction terms found an increased impact of mental illness on costs in deprived patients. Conclusions: Improving quality of primary care and health promotion in people with a mental illness both for their own sake and to decrease the economic burden on the healthcare system, is of vital importance. Key messages: There is a significant increase in hospital costs for somatic care in patients with a mental illness compared to other patients, in particular in patients who are also deprived. It is necessary to improve primary care and health promotion in mentally ill patients, for their sake and for the sake of healthcare systems.